A study of an effective UPTMCAA website design - Cavizo, Ma. Josefina B.; Talisayon, Serafin D. (Quezon City University of the Philippines Diliman, Technology Management Center, 2014)
The TMCAA is an organization that needs collaboration from its community. To communicate with the alumni is very difficult after graduation, the alumni association remains inactive. There is a need for the TMCAA to differ their approach in connecting with the TMC community especially the alumni. Effective communication and collaboration are the keys to revamp the organization. Making use of the internet as a tool for collaboration is the best option for collaboration among organizations especially for an alumni association.
Social networking sites are effective tools for collaboration and integration among organizations, but id does not offer all the features that are needed to support an alumni association. Not all people would like their profile information to be published on the internet, especially in social networking sites. An alumni website is developed by colleges and universities because it promotes the organization in a formal and exclusive way and it serves as an online portal for the organization that will secure the members' profile information.
The purpose of this study is to create an effective design for TMCAA website. The effectiveness of the design of the TMCAA website will support the goals of the organization, which is to encourage members of the alumni, students and faculty to use the website as a tool for collaboration and integration. The alumni website will serve as an online portal that will cater the functions and roles of the alumni association and will also engage participation from the students, faculty and the administration of TMC.
The total budget allocation for the study of an effective TMCAA website project is PHP 20,000. The prototype website that was used for the TMCAA website survey was developed by a project team composed of TMC students for their ITPM class, and the website was submitted in March 2013 as deliverable for their Integrated Project Notebook. The original scope of the website included all the stages of web development : initiating, planning, and designing, development and testing, and closing or deployment. However, due to time and budget constraints, the design was the only phase included in this study.
The features of the web environment or interface and the features of the website are the important aspects of designing the TMCAA website. The key features of the web interface and the website itself are determined from the integration of he study on how to create an effective website, the functions and roles of an alumni association, and the results from the TMCAA survey using the prototype TMC website. The result of this integration formulates an effective website design that will be used for the development of the TMCAA website.
In partial fulfillment of the requirements of TM 299.
Thesis
Keywords: Web site development industry